German-Turkish Friendship: about the Necessity of Including Migrant Literature into the Intercultural Learning - Reinhold, Utri (Glottodidactica, 2010)
Every culture contains foreign elements, e.g. music. However, the strangeness of another culture can also find rejection of people towards it (examples in the latest history). In Germany the Turks were invited by an international contract to do the “dirty” work, but were exploited by the German employees. This was discovered by the work of Walraff. The multiculturalism is a fact that nobody can deny anymore. That is the reason why certain topics concerning immigrants and foreign cultures should appear in schools, especially in teaching literature. The literature of or about immigrants, especially the Turks, and its possibly fertile effects for intercultural understanding are discussed in the article.